General practitioners' perceptions of distributed leadership in providing integrated care for elderly chronic multi-morbid patients: a qualitative study - Harald Braut; Olaug Øygarden; Marianne Storm; Aslaug Mikkelsen (BMC, 2022)
Abstract Background Distributed Leadership (DL) has been suggested as being helpful when different health care professionals and patients need to work together across professional and organizational boundaries to provide integrated care (IC). This study explores whether General Practitioners (GPs) adopt leadership actions that transcend organizational boundaries to provide IC for patients and discusses whether the GPs' leadership actions in collaboration with patients and health care professionals contribute to DL. Methods We interviewed GPs (n = 20) of elderly multimorbid patients in a municipality in Norway. A qualitative interpretive case design and Gioia methodology was applied to the collection and analysis of data from semi-structured interviews. Results GPs are involved in three processes when contributing to IC for elderly multimorbidity patients; the process of creating an integrated patient experience, the workflow process and the process of maneuvering organizational structures and medical culture. GPs take part in processes comparable to configurations of DL described in the literature. Patient micro-context and health care macro-context are related to observed configurations of DL. Conclusion Initiating or moving between different configurations of DL in IC requires awareness of patient context and the health care macro-context, of ways of working, capacity of digital tools and use of health care personnel.